2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--27710
|View full text |Cite
|
Sign up to set email alerts
|

Board # 121 : A Seven-Year Study of Middle and High School Teachers Participating in Research Experiences For Teachers Programs: Exploring the Relationship Between Teacher Performance and Student Achievement

Abstract: Research identifies a national urgency to improve teacher performance and student achievement in science and engineering. This paper responds to this need and presents the results of seven-years of Research Experience for Teachers (RET) programs funded by the National Science Foundation in which engineering faculty collaborate with middle and high school teachers and their students. One program (3 years) is a comprehensive teacher professional development program in which middle school teachers participate in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…, 2015; Miranda and Damico, 2015; Blanchard and Sampson, 2017; Hardré et al. , 2017; Ragusa and Juarez, 2017); and K–12 assessments (Silverstein et al. , 2009; Yelamarthi et al.…”
Section: Discussion Implications and Directions For Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…, 2015; Miranda and Damico, 2015; Blanchard and Sampson, 2017; Hardré et al. , 2017; Ragusa and Juarez, 2017); and K–12 assessments (Silverstein et al. , 2009; Yelamarthi et al.…”
Section: Discussion Implications and Directions For Future Researchmentioning
confidence: 99%
“…One of the most extensive studies among the collection was a 7-year longitudinal study involving 10,468 participants (Ragusa and Juarez, 2017). This work examined the impact of two TRE programs, reporting on the combined results of both programs on in-service teachers and their students, using an observational rubric to examine teaching performance and a Science Teaching Efficacy Beliefs Instrument (Enochs and Riggs, 1990) and K–12 student science reading and concept inventory assessments.…”
Section: Discussion Implications and Directions For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies with firsthand accounts from engineering TRE participants found that their students showed increased subject awareness and increased interest in pursuing an engineering career (Autenrieth et al, 2018;Reynolds et al, 2013). Studies on conceptual learning of students of TRE teachers showed increased pre-/post-content knowledge (Ragusa & Juarez, 2017;Yang et al, 2020). One study has shown that students of TRE teachers outperform students of non-TRE teachers in the New York Regents exam (Silverstein et al, 2009).…”
Section: Teacher Research Experiencesmentioning
confidence: 99%